Diagnostic stewardship for Clostridioides difficile testing in an acute care hospital: A quality improvement intervention - Madeline L. Berg; Ashley M. Ayres; David R. Weber; Melissa McCullough; Victoria D. Crall; Casey L. Lewis; Abby L. Valek; Lizabeth A. Vincent; Joseph Penzelik; Crystal A. Sasinoski; Amanda L. Cheng; Claire F. Bradford; et al. (Cambridge University Press, 2023)
Abstract Objective: To evaluate the impact of a diagnostic stewardship intervention on Clostridioides difficile healthcare-associated infections (HAI). Design: Quality improvement study. Setting: Two urban acute care hospitals. Interventions: All inpatient stool testing for C. difficile required review and approval prior to specimen processing in the laboratory. An infection preventionist reviewed all orders daily through chart review and conversations with nursing; orders meeting clinical criteria for testing were approved, orders not meeting clinical criteria were discussed with the ordering provider. The proportion of completed tests meeting clinical criteria for testing and the primary outcome of C. difficile HAI were compared before and after the intervention. Results: The frequency of completed C. difficile orders not meeting criteria was lower [146 (7.5%) of 1,958] in the intervention period (January 10, 2022-October 14, 2022) than in the sampled 3-month preintervention period [26 (21.0%) of 124; P < .001]. C. difficile HAI rates were 8.80 per 10,000 patient days prior to the intervention (March 1, 2021-January 9, 2022) and 7.69 per 10,000 patient days during the intervention period (incidence rate ratio, 0.87; 95% confidence interval, 0.73-1.05; P = .13). Conclusions: A stringent order-approval process reduced clinically nonindicated testing for C. difficile but did not significantly decrease HAIs.